Explaining the Knowledge and Attitudes of Medan City Residents in Using Telemedicine During the COVID-19 Pandemic - Nadroh Br Sitepu; Tasya Sevrina (Jurnal Penelitian Farmasi Indonesia, 2022)
Coronavirus disease 2019 (COVID-19) is a transmissible respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Governments should encourage telemedicine, the use of technology that combines information and communication with medical expertise to deliver health services, and the ability to diagnose and administer medical care without being held in confined spaces or remote locations. We are calling on the public to start consultations on. Study this aim for knowing description knowledge and attitude the people of Medan City in utilising telemedicine during the COVID-19 pandemic. Method study character survey descriptive, taking sample use method purposive sampling with amount sample as many as 99 respondents. Research results show that the level of knowledge of the people of Medan City against telemedicine with categories good (86.9%), enough good (10.1%), and less good (3%). Attitude level the people of Medan City utilise telemedicine with categories good (66.7%), enough good (32.3%), and less good (1%). The study this is description level knowledge and attitude the people of Medan City are in category good.